Analysis of Correctional Institution Officer Interaction Patterns and Stress During Implementation of Correctional Revitalization in Nusakambangan Indonesian - Anwar, Umar; Hamzah, Imaduddin; Biafry, Vivi Silviani; Aulia, Qisthina (CV. Literasi Indonesia, 2024)
The implementation of correctional revitalization is not only related to structural adjustments and security protocols at Super Maximum Security (SMAX), Maximum Security (MAX), and Medium Security (MS) correctional facilities; it may also have an impact on changes in officer-inmate interaction patterns and the psychological stress officers. After the implementation of institutional revitalization, this study intends to investigate the patterns of officer-inmate interaction and the levels of stress experienced by correctional institution personnel in Nusakambangan with various degrees of security. Eight officers were interviewed as part of the research approach, which involved descriptive qualitative analysis, in four prisons on Nusakambangan Island. The analysis's findings give an example of the many ways that SMAX, MAX, and MS prison guards and convicts engage with one another. Because of restrictions on prisoners' freedom of movement, the implementation of security measures, and disparities in treatment within the development program, different interaction patterns result. Comparing convicts in XMAX and MAX prisons to those in MS prisons, authorities believe that MS prisoners spend more time outside of their rooms engaging in activities, which could compromise security and order. The result is that because inmates in MS prisons are free to roam the facility, but inmates in SMAX and MAX prisons engage in more activities in their quarters, the stress level for officers in MS prisons is higher than the stress level in SMAX and MAX prisons.